2007
DOI: 10.1017/s0022112007004703
|View full text |Cite
|
Sign up to set email alerts
|

Mechanics of merging events for a series of layers in a stratified turbulent fluid

Abstract: This study attempts to explain the evolutionary pattern of a series of well-mixed layers separated by thin high-gradient interfaces frequently observed in stratified fluids. Such layered structures form as a result of the instability of the equilibrium with uniform stratification, and their subsequent evolution is characterized by a sequence of merging events which systematically increase the average layer thickness. The coarsening of layers can take one of two forms, depending on the realized vertical buoyanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
71
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(77 citation statements)
references
References 30 publications
6
71
0
Order By: Relevance
“…For instance, Merryfield (2000) suggested that staircases represent the ultimate state of thermohaline interleaving, which is, in turn, induced by lateral temperature and salinity gradients. Radko (2003) on the other hand argued that doublediffusive layering is likely to be caused by the so-called gamma instability, which is driven by variations in the ratio of the turbulent heat and salt fluxes:…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, Merryfield (2000) suggested that staircases represent the ultimate state of thermohaline interleaving, which is, in turn, induced by lateral temperature and salinity gradients. Radko (2003) on the other hand argued that doublediffusive layering is likely to be caused by the so-called gamma instability, which is driven by variations in the ratio of the turbulent heat and salt fluxes:…”
Section: Introductionmentioning
confidence: 99%
“…To model staircases, several distinct scales must be resolved: (i) fingering interfaces (;1 m), (ii) the vertical thermocline scale (;1 km), and (iii) the lateral basin-scale circulation patterns (;1000 km). Theoretical arguments (Radko 2005) suggest that while the initial layers form rather rapidly (within weeks), the evolution and ultimate equilibration of staircases occur on the time scale of decades. Computational capabilities have only recently reached the level of resolving such a wide range of spatial and temporal scales.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it is worth not-ing that the 2-D models of double-diffusive interleaving, as applied to typical baroclinic fronts in the ocean, are able to forecast intrusive layers with vertical length scale of no more than 10 m (Kuzmina and Rodionov, 1992;May andKelley, 1997, 2001;Kuzmina and Zhurbas, 2000;Kuzmina and Lee, 2005;. Therefore, despite the proven-by-simulation hypothesis of intrusions of small vertical scale merging into larger structures (Radko, 2007), new approaches to the mathematical description of the formation of large intrusions in the area of baroclinic fronts become relevant.…”
Section: Introductionmentioning
confidence: 99%
“…So far, most of these models have focused on the properties of the interfaces between layers, such as their thickness, the heat and mass flux through them, and the characteristic dimensionless ratios. Attempts to determine the conditions for the formation of double-diffusive layers, the layer thickness and their stability [Huppert, 1971;Kelley, 1984] have been proposed for the diffusive and the salt finger regimes [Radko, 2003[Radko, , 2005, and theoretical considerations have been formulated to explain the layer merging mechanisms [Radko, 2007;Noguchi and Niino, 2010b;Radko et al, 2014a]. However, coupling local dynamics and largescale effects in the description of the process by which the typical staircase structure forms and evolves is still an unresolved task.…”
Section: Introductionmentioning
confidence: 99%